Immunopathogenesis and serological markers in Inflammatory Bowel Diseases - Wencan, Zhang; Nizheharodava, Darya; Zafranskaya, Marina (Журнал Белорусского государственного университета. Экология, 2024)
Inflammatory Bowel Diseases (IBDs), encompassing Crohn’s Disease (CD) and Ulcerative Colitis (UC), presents significant diagnostic and therapeutic challenges. The pathogenesis of IBDs, including CD and UC, involves the presence of pathogenic factors such as abnormal gut microbiota, immune response dysregulation, environmental changes, and gene variants. Although many investigations have tried to identify novel pathogenic factors associated with IBDs that are related to environmental, genetic, microbial, and immune response factors, a full understanding of IBDs pathogenesis is unclear. Cytokines have a crucial role in the pathogenesis of IBDs, where they control multiple aspects of the inflammatory response. The role of cytokines produced by innate and adaptive immune cells, as well as their relevance to the future therapy of IBDs are very important. Through a comprehensive analysis of the literature, we highlight the importance of antibodies such as Anti-Saccharomyces cerevisiae Antibodies (ASCA) and Perinuclear Anti-Neutrophil Cytoplasmic Antibodies (pANCA) in distinguishing between CD and UC, predicting disease behavior, and guiding treatment decisions. Despite the progress, the need for markers with improved specificity and sensitivity is evident. This review explores immunopathogenesis and the role of serological markers in IBDs management, discusses current challenges, and anticipates future research directions. The review concludes with an optimistic outlook on the role of microbiota and cytokine in pathogenesis of IBDs, potential of novel biomarkers, personalized medicine, and the integration of advanced technologies to transform IBDs management.